The integral roles of supporting staff in bolstering academic performance: A qualitative study in Vietnamese higher education institutions - Thanh Thao Le; Hoang Yen Phuong; Trut Thuy Pham; Anh Thi Nguyen; Thi Anh Thu Huynh; Huong Tra Nguyen (Cogent Arts & Humanities, 2023)
This scholarly examination qualitatively probes the pivotal functions of supporting staff in enhancing academic performance within higher education in Vietnam’s Mekong region. The research design involved purposive sampling of 10 participants from two different higher education institutions in the Mekong region of Vietnam. Five were academic staff members, including lecturers and professors, and the other five were supporting staff involved in various departments like administration, human resources, and technical support. Participants were engaged in focus-group discussions, which were transcribed and analyzed thematically to elicit a nuanced understanding of the research questions. Utilizing focus-group discussions and semi-structured interviews, it provides deep insights into the intricate dynamic between academic and non-academic roles. The study emphasizes the multifaceted contributions of supporting staff who function as stress reducers, knowledge conduits, role integrators, infrastructural overseers, and administrative efficiency boosters, among others. It calls for policy modifications that recognize and exploit the varied roles of auxiliary personnel in higher education institutions. The study also discusses implications for stakeholders like institutions, staff, policymakers, and researchers, while suggesting potential areas for further exploration. This research enriches existing literature by offering a detailed understanding of supporting staff roles within the Vietnamese higher education context.